Psychological Distress and Quality of Life in Hepatitis Patients: The Mediating Role of Hope (Journal of Asian Development Studies, 2024)
This study examined the association between psychological distress, hope, and quality of life in patients with hepatitis. A correlational research design was employed, and 200 hepatitis patients (100 males & 100 females) were chosen using purposive sampling from various hospitals in Faisalabad city. The variables were evaluated using the Kessler psychological distress scale, hope index, and quality of life scale. The data was analyzed using the Statistical Package for Social Sciences (SPSS). The results indicate a substantial negative association between psychological distress and both hope and quality of life, and a strong positive association between hope and life quality. The finding of the mediation analysis also showed that hope was a significant partial mediator in the association between psychological distress and quality of life. The t-test analysis revealed no statistically significant variations in the mean scores for psychological distress, hope, and quality of life between man and women hepatitis patients. The findings of the present research have implications for a range of health-related areas, including the use of the study findings by healthcare professionals in treating patients suffering from life-threatening chronic conditions such as hepatitis.